Quantifying mean peak running intensities in elite field hockey - Delves, R. I.; Bahnisch, J.; Ball, K.; Duthie, G. M. (The Journal of Strength and Conditioning Research, 2021)
To replicate match demands in training, field hockey (FH) coaches typically prescribe intensities based on whole-match data. Such data may underestimate peak competition periods, potentially underpreparing athletes for competition. This study then aimed to quantify maximal mean running intensities during elite FH competition to facilitate enhanced training prescription. Ten-Hertz Global Positioning System data were collected from 17 male and 11 female FH athletes who competed in the 2016 and 2017 Australian Hockey League tournaments. Maximal mean values for speed, acceleration, and metabolic power (Pmet) were calculated over a 1- to 10-minute moving average by position. Summary match statistics were also analyzed. Linear mixed models were constructed to determine the effect of position on moving average and summary variables. Pairwise comparisons between groups were made using magnitude-based inferences. In female competition, speed and Pmet intensities were greater in midfielders, whereas defenders were lowest in acceleration demands over the 10-minute window and in corresponding intercepts. In male competition, acceleration was greater in defenders during the 10-minute window and in subsequent intercepts compared with midfielders, whereas defenders were lowest in speed intercepts. In comparison with previously reported summary match variables, intensities from the 1-minute moving average interval were 50-65% greater in male competition and 30-50% greater in female competition. The 10-minute moving average framework has identified FH running intensities that are greater than previously reported whole-match averages. This information enhances the understanding of the demands of FH, assisting practitioners to prepare their athletes for the most demanding instances of play.